Effect of Giving A Combination of ROM and Mirror Therapy to Increase The Muscle Strength of the Upper Limb - Dedi Irawandi (Journal of Global Pharma Technology, 2020)
Background:One of the problems in stroke patients is a decrease in muscle strength due to hemiparesis which affects the client's self-acceptance. The study aims is to determine the effectiveness of  combination mirror therapy and ROM on upper limb muscle strength and self-acceptance stage in stroke clients with hemiparesis.Materials and Methods:Quasi experimental research with pre-post control group design was done on 36 respondents with consecutive sampling technique, for 3 months in the stroke room. Upper limb muscle strength was measured using a Medical Research Council scale, while the self-acceptance stage used a self-acceptance stage questionnaire based on the Kubler Ross adaptation stage. Data were analyzed using wilcoxon and Mann-Witney test with p value <0,05.Results: Wilcoxon test known p value <0.05 for muscle strength and self-acceptance stage both in the treatment group and in the control group. The result of analysis of muscle strength difference between treatment group and control is known p value = 0.000, while for self-acceptance stage known p value <0,05 for denial, anger, bargaining and depression, At acceptance stage known p value 0,05. This analysis shows that there is a significant difference in muscle strength and self-acceptance at the denial, anger, bargaining and depression stages after being given a combination of mirror and ROM therapy with stroke clients given ROM therapy alone.Conclusion: Combination of mirror therapy with ROM can be used as nursing intervention in the hospital, especially on ischemic stroke clients with hemiparesis to increase muscle strength and self-acceptance of client